2012
DOI: 10.1371/journal.pone.0036405
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Differentiation of Embryonic Stem Cells into Mesodermal Precursors by BMP, Retinoic Acid and Notch Signalling

Abstract: The ability to direct differentiation of mouse embryonic stem (ES) cells into specific lineages not only provides new insights into the pathways that regulate lineage selection but also has translational applications, for example in drug discovery. We set out to develop a method of differentiating ES cells into mesodermal cells at high efficiency without first having to induce embryoid body formation. ES cells were plated on a feeder layer of PA6 cells, which have membrane-associated stromal-derived inducing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 46 publications
(72 reference statements)
2
35
0
1
Order By: Relevance
“…Estrach et al found that the deletion of jagged1 inhibited hair growth and prevented new hair follicle formation, revealing the interaction of the Wnt and Notch signaling pathways in regulating hair follicle cycle maintenance 31. In general, Notch signaling plays a key role in regulating the self-renewal, proliferation, and differentiation of stem cells 32-34. Previous studies have documented that Notch was widely expressed in developing or differentiating hairs, led to the aberrant differentiation of the hair cortex 35-36, and inhibited the terminal differentiation of the epidermis 37.…”
Section: Discussionmentioning
confidence: 99%
“…Estrach et al found that the deletion of jagged1 inhibited hair growth and prevented new hair follicle formation, revealing the interaction of the Wnt and Notch signaling pathways in regulating hair follicle cycle maintenance 31. In general, Notch signaling plays a key role in regulating the self-renewal, proliferation, and differentiation of stem cells 32-34. Previous studies have documented that Notch was widely expressed in developing or differentiating hairs, led to the aberrant differentiation of the hair cortex 35-36, and inhibited the terminal differentiation of the epidermis 37.…”
Section: Discussionmentioning
confidence: 99%
“…As an agent used to induce in vitro lineage-specific differentiation of ESCs, RA induces in vitro differentiation of ESCs into a number of cell types, including neural (Kim et al 2009;Wichterle et al 2002), mesodermal (Kennedy et al 2009;Torres et al 2012), epithelial (Metallo et al 2008), pancreatic (Shim et al 2007), and germ cell lineages (Chen et al 2012). Our results showed that the differentiation patterns of O. dancena ESC-like cells were distinct at the morphological level depending on the presence or absence of RA.…”
Section: Discussionmentioning
confidence: 62%
“…Kashani, et al () suggested that RA can induce differentiation of mouse BM‐derived CD15+, Oct4+, and CXCR4+ cells into male germ cells in vitro. Moreover, BMPs play an important role in regulation of stem cell fate in mammals (Torres, Prieto, Durupt, Broad, & Watt, ). PGC formation in epiblast cultures can be induced by human recombinant BMP4 (Okamura, Hayashi & Matsui, ), and Bmp4 null mutants have the most severe defect in germ cell development, with a near‐complete absence of PGCs (de Sousa et al, 2004).…”
Section: Discussionmentioning
confidence: 99%